A Pregnant Women’s Group: Its Effects on Maternal and Neonatal Health Care Services among Disadvantaged Community in Makawanpur, Nepal - Shrestha, Bhagawan Das (Journal of Advanced Academic Research, 2017)
In Nepal, the utilization of maternal, newborn and child health (MNCH) care services exhibit big gaps between rich and poor, for instance poorest quintile is at 10.7% skill births attendant services but richest at 81.5%, despite the services being free of cost. Pregnant women group (PWG) approach was initiated to address MNCH inequities prevailing in the disadvantaged community. The PWG is a socially cohesive peer support group of 8-15 pregnant women and postnatal mothers who meet monthly for participatory teaching and learning sessions on MNCH cares and semi-annual publicly group commitment meetings. At the meetings, husbands and mothers-in-law verbally commit to support their pregnant wives and daughters-in-law in present of pregnant women. Local health staff also commits to provide those services. Retrospective cohort study was undertaken in which 449 randomly selected recently delivered women who were members of PWG in last pregnancy and next 449 non-members to PWG from same villages of Makwanpur were introduced the structured questionnaires between March and April 2015. The results indicated that the increase in the utilization of MNCH care services was statistically significant (P